Democracy, Leadership and Development Examined in Light of Nigerian Democracy - Kingsley Patrick Omoruyi (Journal of Southern Sociological Studies, 2026)
The persistent crisis of governance and leadership in Nigeria has limited the capacity of democratic institutions to generate sustainable and human-centered development. This paper examines the interrelationship among democracy, leadership, and development and argues that democratic governance becomes meaningful only when it advances the common good, public accountability, and people’s material well-being. Situated within Southern sociology and Global South scholarship, the paper rejects the tendency to evaluate Nigeria merely as an incomplete version of Euro-American democracy. Instead, it interprets Nigeria as a historically constituted postcolonial formation shaped by colonial state-making, unequal incorporation into global capitalism, local political struggles, and indigenous aspirations for self-reliance. The study adopts qualitative analysis, hermeneutical interpretation, and thematic engagement with secondary literature. It finds that weak political will, corruption, elite capture, fragile institutions, and limited citizen participation obstruct the relationship between democratic leadership and development. At the same time, African intellectual traditions emphasize that development should be understood not simply as economic growth or institutional imitation, but as social transformation grounded in dignity, collective welfare, freedom, and the capacity of people to shape their own futures. The Nigerian case therefore contributes to Southern theory by showing that democracy should be evaluated through historically grounded and substantively social indicators, including access to healthcare, education, water, energy, employment, security, fair taxation, and the rule of law. The paper concludes that responsible leadership and sustainable development require democratic accountability, popular participation, epistemic inclusion, and recognition of locally grounded knowledge. It recommends people-centered governance, stronger institutions, equitable resource distribution, effective leadership training, and the protection of citizens’ rights and freedoms.